Numerical study of PCM integration impact on overall performances of a highly building-integrated solar collector. (July 2019) - Motte, F.; Notton, G.; Lamnatou, Chr; Cristofari, C.; Chemisana, D.
Abstract: In this article, heat loss reduction and overall performances improvement of a solar collector by using Phase Change Material (PCM) are examined. In authors' previous studies, a building-integrated solar collector has been presented with an experimental characterisation and a validated numerical model. In addition, thermal losses at high reduced temperatures were identified due to the specific collector shape. On the other hand, several authors introduced PCM thermal storage for domestic hot water systems (DHWS). In the frame of the present study, the goal is to use the high PCM volumetric thermal density for limiting both temperature and thermal losses and recovering a part of the stored heat during evening. Adding PCM might change the optimum operating conditions: the influence on monthly performances of existing PCM characteristics, flow rate variation, temperature regulation and PCM volume addition are investigated. Simulations for a complete DHWS have been performed with measured environmental data (solar radiation, wind, ambient temperature). The mathematical model of PCM thermal process is presented. The performances with PCM addition are evaluated and the improvements on the thermal behaviour are estimated. In addition, Life Cycle Assessment (LCA) is performed in order to examine the influence of PCM use on the environmental profile of the solar system. Highlights: Myristic acid 51 chosen between 9 tested PCMs. Annual Solar fraction improvement by 6.10 %: +10% in summer and -0.5%, in winter. Calculation of the flow rate and PCM thickness maximizing the thermal performances. Life Cycle Analysis: the PCM utilization reduces the EPBT by 0.6 year. Low performance gain with an over cost and complications of using PCM.